New drugs, fair prices managing the pharmaceutical innovation ecosystem for sustainable and affordable new medicines - Smith, Brian D. (2023)
New Drugs, Fair Prices addresses the important question of how we might get the innovative new medicines we need at prices we can afford. Today, this debate is impassioned but sterile. One side calls for price controls, discounting their impact on investment in innovation. The other points to miraculous new therapies, disregarding their affordability and social inequity. This polarized argument creates more heat than light, threatening the social contract between the industry and society on which we pharmaceutical innovation depends. This ground-breaking book takes a wholly new perspective on the issue and raises the debate to a more informed and productive level. Drawing on interviews with more than 70 experts across the pharmaceutical innovation world and combining a diverse literature from scientific, political, economic and business domains, it describes how a sustainable and affordable supply of new medicines is possible only by balancing pharmaceutical innovation's complex, adaptive ecosystem. By considering how each of the ecosystem's seven habitats work and interact with each other, it makes a comprehensive set of recommendations for achieving that ecosystem balance. The core message of New Drugs, Fair Prices is important to anyone who ever has needed or will ever need a medicine: we can have a sustainable supply of new medicines that are both innovative and affordable if we manage the pharmaceutical innovation ecosystem intelligently"--